2006
DOI: 10.1109/lawp.2006.886305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Characterization of a High-Performance Ka-Band Surface Micromachined Elevated Patch Antenna

Abstract: Abstract-A novel Ka-band surface micromachined air-elevated patch antenna is designed, fabricated and characterized. It demonstrates a 10.5% 10-dB fractional bandwidth and 9.5 dBi directivity for an elevation of 600 µm. The elevated patch is fed by a vertical epoxy-core metal-coated micromachined probe and supported by several epoxy posts underneath. By the unique feeding technique and the substrate removal approach that are presented in this paper, the performance degradation for traditional microstrip antenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The wideband operation was achieved by optimally tuning resonance associated with the coupling slot by optimizing its dimensions. The bandwidth of the antenna device was determined to be %, almost a factor of 2 larger than the figure of 10.5% obtained for the probe fed device [1]. The high-gain patch antenna and the associated method of integration onto microwave substrates could have potentially important applications in the emerging field of UWB networks.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The wideband operation was achieved by optimally tuning resonance associated with the coupling slot by optimizing its dimensions. The bandwidth of the antenna device was determined to be %, almost a factor of 2 larger than the figure of 10.5% obtained for the probe fed device [1]. The high-gain patch antenna and the associated method of integration onto microwave substrates could have potentially important applications in the emerging field of UWB networks.…”
Section: Discussionmentioning
confidence: 77%
“…This has attracted significant research effort in developing high performance antenna devices using alternative fabrication methods. The shown that the gain and efficiency of antennas can be improved considerably by using partial and complete substrate independent antenna designs [1]. This is achieved by creating an air gap or cavity between the substrate surface and the radiating patch [1]- [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations